Breastfeeding in Islamic perspective: a thematic analysis - Jamil, Nurul Akma; Muda, Siti Mariam; Ismail, Hamizah (2016)
Introduction: Breastfeeding was mentioned in several verses in the Al-Quran. The verses in Surah Al-Baqarah emphasized parents’ responsibility to provide breast milk during the first two years of life. However, there is no specific rule about the exact time to wean a child as long as his/her wellbeing is not being compromised. As the decision to breastfeed was influenced by social and cultural context; this study aimed to explore Muslim mothers’ understanding on breastfeeding according to medical needs and Islamic perspective.